Using random subcarrier weighting for multi-carrier systems physical layer security - Zhou ZHONG; Liang JIN; Kai-zhi HUANG (Tongxin xuebao)
An OFDM security model and a physical layer security transmission scheme were proposed for multi-carrier systems to achieve low probability of interception.In contrast to the resource allocation algorithm which would be disabled at the low SNR,this method designed the subcarrier transmission weighting vectors to randomize the eavesdropper’s signals but not the authorized receiver’s signals.The channel state information was the only character to distinguish authorized receivers and eavesdroppers,which was conducted to guide the weighting vectors design.Simulation results show that the proposed method guarantees that authorized receiver performs transmitted reference demodulation successfully,while the eavesdroppers can not detect the transmitted symbols.